Simple thiol-ene click chemistry modification of SBA-15 silica pores with carboxylic acids - Bordoni, Andrea Veronica (2015)
A straightforward approach for anchoring tailored carboxylic groups in mesoporous SiO2 colloidal materials is presented. The thiol-ene photochemical reaction between vinyltrimethoxysilane precursors and various thiocarboxylic acids which has, click chemistry features (i.e. high conversion yields, insensitivity to oxygen, mild reaction conditions), results in carboxylated silane precursors that can be readily used as surface modifiers. The carboxylic groups of acetic, undecanoic and succinic acid were immobilized on the silica mesopore walls of SBA-15 powders employing the synthesized silane precursors. Post-grafting has been confirmed through infrared spectrometry (FTIR), energy dispersive X-ray spectroscopy (EDS), elemental analysis (EA) and zeta potential measurements. Detailed field-emission gun scanning electron microscopy (FESEM) images and small angle X-ray scattering (SAXS) data revealed parallel mesopores and ordered mesostructures. It is shown that the immobilized COOH groups are chemically accessible for acid-base reactions as well as copper adsorption. Immobilization of easily synthesized tailored carboxylic modified alkoxide precursors within mesoporous systems provides a unique chemical nanoenvironment within these ordered frameworks.